2021
DOI: 10.31014/aior.1992.04.03.371
|View full text |Cite
|
Sign up to set email alerts
|

Modelling & Forecasting Volatility of Daily Stock Returns Using GARCH Models: Evidence from Dhaka Stock Exchange

Abstract: Modelling volatility has become increasingly important in recent times for its diverse implications. The main purpose of this paper is to examine the performance of volatility modelling using different models and their forecasting accuracy for the returns of Dhaka Stock Exchange (DSE) under different error distribution assumptions. Using the daily closing price of DSE from the period 27 January 2013 to 06 November 2017, this analysis has been done using Generalized Autoregressive Conditional Heteroscedastic (G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Sudah banyak penelitian volatilitas saham yang menggunakan GARCH seperti perbandingan kinerja model GARCH untuk menangkap volatilitas pasar saham di Malaysia (Lim & Sek, 2013); pemodelan volatilitas pasar saham Bulgaria, Chechnya, Polandia, Hungaria dan Turkey (Ugurlu et al, 2014); Sudan dan Mesir (Abdala et al, 2014); Uganda (Namugaya et al, 2014); Kenya (Koima et al, 2015); Bangladesh (Miah & Rahman, 2016); Afrika Selatan dan Tiongkok (Cheteni, 2016); Tanzania (Kazungu & Mboya, 2021). Untuk prediksi volatilitas harga saham menggunakan GARCH sudah ada beberapa penelitian yang dilakukan seperti penelitian terhadap indeks saham S&P-500 (Awartani & Corradi, 2005); akurasi peramalan volatilitas di pasar saham Swedia (Grek, 2014); pemodelan dan peramalan volatilitas di Dhaka Stock Exchange (Ahmed & Naher, 2021); peramalan 21 indeks saham dunia (Sharma, 2015). Penelitian ini bertujuan untuk memprediksi volatilitas IHSG menggunakan GARCH dan berusaha menjelaskan peristiwa yang menyebabkan volatilitas IHSG sepanjang tahun 2022.…”
Section: Pendahuluanunclassified
“…Sudah banyak penelitian volatilitas saham yang menggunakan GARCH seperti perbandingan kinerja model GARCH untuk menangkap volatilitas pasar saham di Malaysia (Lim & Sek, 2013); pemodelan volatilitas pasar saham Bulgaria, Chechnya, Polandia, Hungaria dan Turkey (Ugurlu et al, 2014); Sudan dan Mesir (Abdala et al, 2014); Uganda (Namugaya et al, 2014); Kenya (Koima et al, 2015); Bangladesh (Miah & Rahman, 2016); Afrika Selatan dan Tiongkok (Cheteni, 2016); Tanzania (Kazungu & Mboya, 2021). Untuk prediksi volatilitas harga saham menggunakan GARCH sudah ada beberapa penelitian yang dilakukan seperti penelitian terhadap indeks saham S&P-500 (Awartani & Corradi, 2005); akurasi peramalan volatilitas di pasar saham Swedia (Grek, 2014); pemodelan dan peramalan volatilitas di Dhaka Stock Exchange (Ahmed & Naher, 2021); peramalan 21 indeks saham dunia (Sharma, 2015). Penelitian ini bertujuan untuk memprediksi volatilitas IHSG menggunakan GARCH dan berusaha menjelaskan peristiwa yang menyebabkan volatilitas IHSG sepanjang tahun 2022.…”
Section: Pendahuluanunclassified
“…However, a study on DSE by Abdullah et al (2018) revealed that MA(2)-EGARCH (1,3) offers the most accurate results outside of the sample among its counterparts. According to the results of the student's t distribution and the normal distribution, ARMA (1,1)-IGARCH (1,1) has the best out-of-sample forecasting performance for DSE (Ahmed, Naher, & Ahmed, 2021). Huq and Ali (2018) investigated the fact that the GJR-GARCH (1, 1) under the Gaussian error distribution model outperformed other DSE models.…”
Section: Volatility Forecastingmentioning
confidence: 99%
“…Ahmed & Suliman, 2011), examined modelling stock market volatility using GARCH models evidence from Sudan. The symmetric and asymmetric behavior of the stock was analyzed and the result revealed that the conditional variance process was highly persistent and as such provided evidence of risk premium for the KSE index stock series which showed that the asymmetric model provided a better fit than the symmetric model, which confirmed the presence of leverage effect (Maqsood et al, 2017).…”
mentioning
confidence: 99%